Faculty of Nursing, Universitas Airlangga, Surabaya, Indonesia. - Bakar, Abu; Khusniyah, Indah Mahmudah; Pratiwi, Ika Nur (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to assess the effectiveness of the influence of listening to Asmaul Husna (the names of God are beautiful, good, great, and noble), isometric handgrip exercise, and foot hydrotherapy interventions on blood pressure in elderly with hypertension. Background: Hypertension or high blood pressure often appears without symptoms, so it is called a silent killer. Based on these problems, non-pharmacological methods can reduce blood pressure, namely the intervention of listening to Asmaul Husna, isometric handgrip exercise, and foot hydrotherapy. Method: Quasi-experimental research design with pre-post test control group design involving 60 respondents using probability sampling techniques. The independent variable in this study was listening to Asmaul Husna, isometric handgrip exercise, and foot hydrotherapy intervention, while the dependent variables were systolic, diastolic blood pressure, and pulse. The data obtained were then analyzed using the Independent t-Test or Wilcoxon Signed Rank Test and Mann Whitney with a degree of significance α ≤ 0.05. Results: Results of data analysis using the Independent t-Test statistic in the treatment group and control group were, for pulse (p = 0.000). The results of tests with Mann Whitney obtained the following result for systolic (p = 0.000) and diastolic (p = 0.000), which means that there were changes in systolic, diastolic, and pulse before and after listening to Asmaul Husna, isometric handgrip exercise, and foot hydrotherapy. Discussion: Listening to Asmaul Husna, isometric handgrip exercise, and foot hydrotherapy interventions have positive benefits for reducing systolic and diastolic blood pressure, and pulse in the elderly with hypertension. For further research, the researchers suggest that more studies about the effectiveness of this intervention should be conducted by increasing the number of dependent variables.